2018
DOI: 10.1123/jmld.2016-0067
|View full text |Cite
|
Sign up to set email alerts
|

Do Irish Adolescents Have Adequate Functional Movement Skill and Confidence?

Abstract: Original citationAccess to the full text of the published version may require a subscription. Rights

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
45
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(56 citation statements)
references
References 46 publications
(44 reference statements)
9
45
2
Order By: Relevance
“…A previously developed tool to assess perceived functional movement competence amongst an Irish adolescent population was employed in this study to measure the PMC of participants in their functional movement proficiency [ 22 ]. As per the FMS scale outlined above, small modifications were made to refer to ‘how well can you perform’, rather than ‘how confident you are’, which is in accordance with the recommended alignment between PMC and FMS assessment [ 59 ].…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…A previously developed tool to assess perceived functional movement competence amongst an Irish adolescent population was employed in this study to measure the PMC of participants in their functional movement proficiency [ 22 ]. As per the FMS scale outlined above, small modifications were made to refer to ‘how well can you perform’, rather than ‘how confident you are’, which is in accordance with the recommended alignment between PMC and FMS assessment [ 59 ].…”
Section: Methodsmentioning
confidence: 99%
“…Similar to the McGrane et al (2016) protocol, participants were asked to rate their competence at performing the identified seven FMS™ tasks, based on a Likert-scale format of 1–10, in which a score of 1 indicated being not at all competent, and a score of 10 indicated being very competent. As the seven FMS™ tasks are non-sport specific and participants may not be familiar with the movements, a visual image alongside the question was provided, similar to empirically validated pictorial instruments for assessing FMS perceived competence [ 22 , 61 , 62 ]. Previous test–retest reliability coefficients for this perceived functional movement competence scale ranged from 0.82 to 0.93, which showed that the scores across this instrument were stable over time [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations